IDENTIFYING STUDENTS' LEARNING MOTIVATION AT THE START OF FACE-TO-FACE LEARNING POST COVID-19 PANDEMIC IN DENPASAR CITY - I Ketut Manik Asta Jaya (UHN IGB Sugriwa Denpasar, 2023)
This research aims to identify the level of students' learning motivation as they return to face-to-face learning in Denpasar City. This study is important for educators in making policy decisions to develop appropriate learning strategies and optimize students' learning motivation. The research falls under the category of quantitative research, employing a survey method distributed through Google Forms. The sample for this study consisted of 32 respondents who were sixth-grade students in elementary schools. The sample was determined using random sampling technique, selecting two schools from each of the four districts in Denpasar City. The research findings indicate that the learning motivation of elementary school students at the beginning of face-to-face learning post-COVID-19 pandemic in Denpasar City is categorized as good. This can be observed from the average percentage of respondents' answers for all indicators, which is 77.62 percent. However, several issues were also identified, such as the lack of motivation among students to improve learning outcomes and the limited awareness of utilizing the school library for reading purposes.